2000
DOI: 10.1021/es990098l
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Use of Partitioning and Interfacial Tracers To Determine the Content and Mass Removal Rates of Nonaqueous Phase Liquids

Abstract: It was assessed whether partitioning and interfacial tracers can be used to determine the content and mass removal rate of nonaqueous phase liquid (NAPL) in porous media. Retardation factors for these tracers were determined for five different model matrices contaminated with hexadecane as NAPL. The retardation of the partitioning tracer 2,4-dimethyl-3-pentanol was correlated with the degree of NAPL saturation for four of the five matrices (r  2 = 0.93, n = 8). The observed retardation factors matched the reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Column studies with hexadecane-contaminated matrices were performed as described previously (Noordman et al, 2000b). Stainless steel preparative HPLC columns (length 7.0 cm, i.d.…”
Section: Column Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Column studies with hexadecane-contaminated matrices were performed as described previously (Noordman et al, 2000b). Stainless steel preparative HPLC columns (length 7.0 cm, i.d.…”
Section: Column Studiesmentioning
confidence: 99%
“…After saturation of the columns by elution with 100 ml min − 1 electrolyte solution using a flow rate of 0.1 ml min − 1 , the concentration of the hexadecane was determined by GC analysis of five 7 ml effluent fractions. Subsequently, tracer experiments were done which lasted for up to 20 pore volumes (Noordman et al, 2000b). The breakthrough profiles of the conservative tracer potassium bromide indicated that the columns were packed homogeneously and that physical non-equilibrium effects were absent.…”
Section: Column Studiesmentioning
confidence: 99%
See 3 more Smart Citations